Microfinance and Its Discontents : Women in Debt in Bangladesh - Karim, Lamia (Book collections on Project MUSE., 2011)
In 2006 the Grameen Bank of Bangladesh won the Nobel Peace Prize for its innovative microfinancing operations. This path-breaking study of gender, grassroots globalization, and neoliberalism in Bangladesh looks critically at the Grameen Bank and three of the leading NGOs in the country. Amid euphoria over the benefits of microfinance, Lamia Karim offers a timely and sobering perspective on the practical, and possibly detrimental, realities for poor women inducted into microfinance operations. In a series of ethnographic cases, Karim shows how NGOs use social codes of honor and shame to shape t.